Efektivitas Penggunaan Media Visual terhadap Keterampilan Menulis Puisi Siswa Sekolah Dasar - Wahyuningsih, Fitri Marliyah; Giwangsa, Sendi Fauzi (AS-SABIQUN, 2025)
Writing poetry is often considered challenging for elementary school students due to a lack of imagination, mastery of diction, and limited use of relevant teaching media. This study aims to examine the effectiveness of using visual media in improving the poetry writing skills of elementary school students. The study employed a quantitative approach with a pre-experimental "one group pretest-posttest" design involving a sample of 9 fifth-grade students from SDN Baros Mandiri 5, selected randomly. Data were collected through pretests and posttests using a poetry writing assessment rubric that included five aspects: diction, figurative language, rhyme, theme coherence, and typography. Data analysis was conducted using a paired t-test. The results showed an increase in the average posttest score (61.7) compared to the pretest score (50.9), with a difference of 10.8 points. The paired t-test yielded a value of t=−5.21 and p<0.001, indicating that the use of visual media was effective in enhancing poetry writing skills. Visual media proved to motivate students, stimulate their imagination, and assist them in creatively expressing their ideas in poetry. However, this study was limited by the small sample size and the absence of a control group, suggesting the need for further research with a more comprehensive design to strengthen the findings.